2014
DOI: 10.5539/jas.v6n7p157
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Hybrid Rice in Bangladesh: Farm Level Experience

Abstract: The purpose of the study was to understand the farmers' response to hybrid rice over the last decade. To achieve this, we used the "diffusion of innovation" model as developed by Rogers. The specific objectives guiding the study were to: i) describe the socio-economic and demographic characteristics of the farmers; ii) survey the varieties of hybrid rice cultivated over the last decade and identify the best performers; iii) assess the extent of adoption of hybrid rice in Bangladesh; iii) investigate the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…By the 2008-09 crop year, only about 8% of the rice area was planted with different rice hybrids (Janaiah & Xie, 2010). On average, farmers brought 37.84% of their potential rice farming area for cultivation of hybrid rice over the period of 2001-2011 in the sample areas (Shah, Grant, & Stocklmayer, 2014). They concluded that there is an enormous potential for improving the level of adoption of hybrid rice in Bangladesh.…”
mentioning
confidence: 99%
“…By the 2008-09 crop year, only about 8% of the rice area was planted with different rice hybrids (Janaiah & Xie, 2010). On average, farmers brought 37.84% of their potential rice farming area for cultivation of hybrid rice over the period of 2001-2011 in the sample areas (Shah, Grant, & Stocklmayer, 2014). They concluded that there is an enormous potential for improving the level of adoption of hybrid rice in Bangladesh.…”
mentioning
confidence: 99%
“…High cost of seed which was also needed to be purchased every year, low price of the hybrid rice per quintal compared to other rice varieties, overlooking the higher production, infestation of the pest and disease were also among the reported problems. Severe infestation of insects and pests and lack of irrigation facilities were the problems faced by farmers revealed in the findings of Singh et al, (2011);Shah et al, (2014b) and (Dasgupta & Roy, 2014).…”
Section: Problems Faced By Hybrid Rice Adopter and Non-adoptermentioning
confidence: 98%
“…Risk aversion is identified as a factor of VI adoption by both Fisher and Kandiwa (2014) and Shah et al (2016). Risk aversion can stem from households' needs for subsistence food, which imply growing more local varieties that are culturally appropriated for food consumption (Smale and Heisey, 1993;Smale et al, 1995;Mariano et al, 2012;Shah et al, 2014Shah et al, , 2016. In this regard, adverse events, such as droughts, that affected crop yields during previous cultivation years have been shown to reduce the share of land cultivated with VI (Adesina and Baidu-Forson, 1995;Mariano et al, 2012;Fisher and Kandiwa, 2014).…”
Section: Contextual Factors: Managing An Uncertain Worldmentioning
confidence: 99%